Subsistence food production practices: An approach to food security and good health - Rankoana, Sejabaledi A (International Journal of Environmental Research and Public Health, 2017)
Food security is a prerequisite for health. Availability and accessibility of food in rural areas is mainly achieved through subsistence production in which community members use local practices to produce and preserve food. Subsistence food production ensures self-sufficiency and reduction of poverty and hunger. The main emphasis with the present study is examining subsistence farming and collection of edible plant materials to fulfill dietary requirements, thereby ensuring food security and good health. Data collected from a purposive sample show that subsistence crops produced in the home-gardens and fields, and those collected from the wild, are sources of grain, vegetables and legumes. Sources of grain and legumes are produced in the homegardens and fields, whereas vegetables sources are mostly collected in the wild and fewer in the home-gardens. These food sources have perceived health potential in child and maternal care of primary health care.
International Journal of Environmental Research and Public Health, 2017, 14,1184
Keywords: self-sufficiency; Traditional foods; subsistence productio; Food security; Health food; Maternal care; Food security; Farming; Agriculture -- Economic aspects